Spiegel’s hernia: Na integrative review (Research, Society and Development, 2023)
Introduction: Spiegel's hernia is a rare protrusion of tissue or organs through a defect in the Spiegel's aponeurosis, which can be congenital or acquired, often with non-specific symptoms. Diagnosis is made using ultrasound or computed tomography. The main treatment is surgical, using modern videolaparoscopic techniques. Complications, such as entrapment and strangulation, occur in up to 30% of cases. Objective: To provide a comprehensive and updated analysis of Spiegel's hernia, addressing its definition, causes, diagnosis and possible clinical consequences. Methodology: This study follows the guidelines of an integrative review, adopting a descriptive and qualitative approach. Results and Discussion: The process for selecting evidence prioritized the most comprehensive and up-to-date materials on the subject of Spiegel's hernia. It is important to emphasize that, although complications are minimally possible, most cases of Spiegel hernia will result in favorable clinical outcomes. Spiegel's hernia tends to have an excellent prognosis after surgical treatment, however adequate medical follow-up is essential to monitor the postoperative period and possible complications. Conclusion: In short, the importance of updated knowledge about Spiegel's hernia, including its definition, causes, diagnosis and possible clinical consequences, is evident. An in-depth understanding of this condition allows for an appropriate approach, offering peace of mind, health and well-being to patients. With the advancement of Medicine, it is expected that new studies and technological advances will continue to improve our knowledge and clinical management of these hernias, providing better results for patients.